Belief without Church and Moral Regulation - Kis, Sandor (Problemos, 1989)
The article deals with the role of the Church and religion in the socialist countries of Middle Europe. Most attention is paid to the phenomenon of residual religiousness, that is to the case when an individual having no regular contacts with religious organizations, nevertheless retains inner links with religious beliefs in the solutions of the problems of world outlook and morality. Social causes and effects of the phenomenon are analysed.